Erasure of Post-Colonial Political Activism in Malawi’s History Education - Bridget Galafa; Thokozani Galafa (UIN Imam Bonjol Padang, 2024)
The History curriculum in Malawi has experienced reforms due to the various political periods that have dictated its direction. The agency for a revised curriculum first appeared upon independence when the country adopted a colonial education system. The paper argues that such a process was hijacked by the then liberation movement that had emerged victorious against white colonial rule – the Malawi Congress Party. This meant erasing narratives that would otherwise challenge the government’s legitimacy and incumbency. Through a review of the current History syllabi which evolved from a 2013 curriculum review and a close reading of the recommended history textbooks, the paper argues that the erasure of such counter-narratives remains intact to this day, basically for the same reasons they were excluded from the initial post-independence curriculum opposition to political hegemony. It, therefore, argues for the re-inclusion of these multiple histories to create complete narratives that have otherwise been fragmented by revisionism.